2003
DOI: 10.1093/ajcn/77.3.559
|View full text |Cite
|
Sign up to set email alerts
|

Addition of inulin to a moderately high-carbohydrate diet reduces hepatic lipogenesis and plasma triacylglycerol concentrations in humans

Abstract: The addition of high-performance inulin to a moderately high-carbohydrate, low-fat diet has a beneficial effect on plasma lipids by decreasing hepatic lipogenesis and plasma triacylglycerol concentrations. These results support the use of nondigestible carbohydrate for reducing risk factors for atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
139
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(155 citation statements)
references
References 40 publications
8
139
0
8
Order By: Relevance
“…Hepatic lipogenesis and TAG synthesis is involved in nonalcoholic fatty liver disease . On the other hand, hepatic TAG synthesis is decreased by OFS in rats, and also in healthy human volunteers (Delzenne & Williams, 2002;Letexier et al, 2003). It would therefore be important to assess a 'dynamic' analysis of fatty acid metabolism through tracer methodology in NASH patients receiving OFS, to approach the biochemical mechanism underlying this effect.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatic lipogenesis and TAG synthesis is involved in nonalcoholic fatty liver disease . On the other hand, hepatic TAG synthesis is decreased by OFS in rats, and also in healthy human volunteers (Delzenne & Williams, 2002;Letexier et al, 2003). It would therefore be important to assess a 'dynamic' analysis of fatty acid metabolism through tracer methodology in NASH patients receiving OFS, to approach the biochemical mechanism underlying this effect.…”
Section: Resultsmentioning
confidence: 99%
“…This merits further investigation. While the doses used in animal studies are not directly transposable to human nutrition, several reports have demonstrated that ingestion of fructo-oligosaccharides at the dose of 5 to 20 g/day are sufficient to promote prebiotic [37][38][39][40] and physiological effects [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, bread is recommended in moderation for diabetic and obese individuals. Studies have shown that besides these population groups, low glycemic index food should be recommended for those harboring heart disease as well as for healthy individuals, as it contributes to better sensitivity to insulin, which it is an important factor concerning the reduction of diabetes development risk (Caruso, Menezes, 2000;Letexier et al, 2003).…”
Section: Introductionmentioning
confidence: 99%